Circadian Rhythm of Vascular Function in Midlife Adults. Issue 6 (June 2019) - Thosar, Saurabh S.; Berman, Alec M.; Herzig, Maya X.; McHill, Andrew W.; Bowles, Nicole P.; Swanson, Christine M.; Clemons, Noal A.; Butler, Matthew P.; Clemons, Aaron A.; Emens, Jonathan S.; Shea, Steven A.
Abstract : Objective—: Adverse cardiovascular events occur more frequently in the morning than at other times of the day. Vascular endothelial function (VEF)—a robust cardiovascular risk marker—is impaired during this morning period. We recently discovered that this morning impairment in VEF is not caused by either overnight sleep or the inactivity that accompanies sleep. We determined whether the endogenous circadian system is responsible for this morning impairment in VEF. We also assessed whether the circadian system affects mechanistic biomarkers, that is, oxidative stress (malondialdehyde adducts), endothelin-1, blood pressure, and heart rate. Approach and Results—: Twenty-one (11 women) middle-aged healthy participants completed a 5-day laboratory protocol in dim light where all behaviors, including sleep and activity, and all physiological measurements were evenly distributed across the 24-hour period. After baseline testing, participants underwent 10 recurring 5-hour 20-minute behavioral cycles of 2-hour 40-minute sleep opportunities and 2 hours and 40 minutes of standardized waking episodes. VEF, blood pressure, and heart rate were measured, and venous blood was sampled immediately after awakening during each wake episode. Independent of behaviors, VEF was significantly attenuated during the subjective night and across the morning ( P =0.04). Malondialdehyde adducts and endothelin-1 exhibited circadian rhythms with increases across the morning vulnerable period and peaks around noon ( P ⩽0.01). Both systolic ( P =0.005) and diastolic blood pressure ( P =0.04) were rhythmic with peaks in the late afternoon. Conclusions—: The endogenous circadian system impairs VEF and increases malondialdehyde adducts and endothelin-1 in the morning vulnerable hours and may increase the risk of morning adverse cardiovascular events in susceptible individuals. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02202811. Abstract : Supplemental Digital Content is available in the text.